Biowaste-Derived Carbon Dots: A Perspective on Biomedical Potentials - Rabiee, Navid; Iravani, Siavash; Varma, Rajender S (Molecules (Basel, Switzerland), 2022)
Today, sustainable and natural resources including biowastes have been considered attractive starting materials for the fabrication of biocompatible and biodegradable carbon dots (CDs) due to the benefits of availability, low cost, biorenewability, and environmentally benign attributes. These carbonaceous nanomaterials have been widely explored in the field of sensing/imaging, optoelectronics, photocatalysis, drug/gene delivery, tissue engineering, regenerative medicine, and cancer theranostics. Designing multifunctional biowaste-derived CDs with a high efficacy-to-toxicity ratio for sustained and targeted drug delivery, along with imaging potentials, opens a new window of opportunity toward theranostic applications. However, crucial challenges regarding the absorption/emission wavelength, up-conversion emission/multiphoton fluorescence mechanisms, and phosphorescence of these CDs still need to be addressed to attain the maximum functionality and efficacy. Future studies ought to focus on optimizing the synthesis techniques/conditions, evaluating the influence of nucleation/growth process on structures/properties, controlling their morphology/size, and finding the photoluminescence mechanisms. Reproducibility of synthesis techniques is another critically important factor that needs to be addressed in the future. Herein, the recent developments related to the biowaste-derived CDs with respect to their biomedical applications are deliberated, focusing on important challenges and future perspectives.
Keywords: Reproducibility of Results; Quantum Dots; uhlík; valorization; Diagnostic Imaging; biomedical applications; biowaste-derived carbon dots; Drug Delivery Systems; biocompatibility; green chemistry; kvantové tečky; diagnostické zobrazování; sustainability; lékové transportní systémy; reprodukovatelnost výsledků; Carbon